PENGELOLAAN PERPUSTAKAAN KUANSING OLEH DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN KUANTAN SINGINGI - Yahdini, Rilly; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The phenomenon identified by researchers in the research of the Kuansing Library Management by the Library and Archives Service of Kuantan Singingi District did not meet the national library standards, namely the absence of technology-based information network services; limited human resources in managing libraries; and the lack of infrastructure. This study aims to determine and analyze library management and the inhibiting factors of Kuansing library management by the Library and Archives Service of Kuantan Singingi Regency. In this study using the theory of George R. Terry in the Hasibuan 2017 management function to analyze the Management of the Kuansing Library by the Library and Archives Service of Kuantan Singingi Regency. This theory consists of Planning, Organizing, Actuating, Controlling. This type of research uses qualitative methods with data collection techniques for interviewing, observation, and documentation. Based on the results of the study it is known that the Management of the Kuansing Library by the Library and Archives Service of Kuantan Singingi Regency has not been optimal in terms of Planning, organizing, implementing and monitoring. Inhibiting factors for the management of the Kuansing Library by the Library and Archives Office of Kuantan Singingi Regency are facilities and infrastructure, the absence of regulations and budget constraints.Keywords: Management, Library, Archives, Standards, National